Analisis faktor pendorong minat nasabah dalam memilih Tabungan Haji di Bank Syariah Mandiri Kantor Cabang Aceh - Nurma Sari; Lika Annisa; Eka Nurlina (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2021)
This study aims to partially and simultaneously analyze the influence of service quality, social, promotion, and knowledge on customer interest in using Hajj savings at Bank Syariah Mandiri in Aceh. Based on 122 questionnaires distributed to respondents, using probability sampling technique, which is simple random sampling and later analyzed by using multiple linear regression models, the results show that service quality, social, promotion, and knowledge have a simultaneous and partial effect on customer interest in using Hajj savings at Bank Syariah Mandiri in Aceh.